NATIVE GOLD OF UKRAINE, PREREQUISITES FOR THE CREATION OF ITS CRYSTALLOGENETIC DETERMINANT - Kvasnytsya, V.; Kvasnytsya, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main developments in the typomorphism of native gold from various depth and uneven-aged deposits are described briefly, and the basis for creating a native gold crystallogenetic determinant of Ukraine is proposed. A significant geological material for the most known occurrences of gold mineralization in Ukraine was collected and processed, and a certain stage of studying the crystallomorphology and chemical composition of visible native gold was completed. The crystals of native gold from the occurrences and deposits on the Ukrainian Shield, the Donbass, in the Ukrainian Carpathians and the Transcarpathia have been characterized. The methods of native gold studying, such as goniometry, scanning electron microscopy, and microprobe analysis were used. The typomorphic features of native gold from the main deposits and ore occurrences of Ukraine are determined, which can be used in the practice of predictive, geological prospecting and prospecting for gold. The native gold of the Ukrainian Shield is attributed to deep mineralization, the Ukrainian Carpathians and the Donbass - to medium-deep mineralization and the Transcarpathia - to shallow mineralization. It is shown that in Ukraine, as in other gold-bearing regions of the world, the transition from an ancient deep and medium deep mineralization to a younger near-surface mineralization increases the number of well-formed crystals of native gold and their morphology becomes more complex, individuals of isometric form are replaced by distorted crystals, the role of dendrites and complex twins increases, the grade of gold becomes lower and its heterogeneity grows, the composition and concentration of impurity elements change. The crystallomorphology of the shallow low-grade native gold of the Transcarpathia is diverse (the Muzhiіve deposit, quartz-barite ores). Unique crystals here are complex twins of cube-octahedrons of native gold. Specificity of medium-deep medium-grade native gold from some ore occurrences of the Donbass is rhombododecahedral faceting of its crystals. Crystallomorphology of deep high-grade native gold from deposits and ore occurrences of the Ukrainian Shield is monotonous. Research data on native gold from known deposits and ore occurrences of Ukraine are generalized and systematization of endogenous gold ore occurrences of Ukraine is made on this basis. A model of a crystallogenetic determinant of native gold of Ukraine is proposed, in which the following main sections are emphasized: 1) native gold mineral associations; 2) chemical-structural and other features of gold crystals; 3) gold crystals morphology; 4) gold crystals anatomy; 5) the method and mechanism of gold crystals growth; 6 ) typomorphic signs of gold crystals; 7) genesis of gold. As an example, a crystallogenetic determinant of native gold from the Proterozoic conglomerates of the Bilokorovychi structure on the Volyn megablock is given. The mineralogical criteria of gold mineralization are outlined and some general conclusions concerning genesis, forecast and searches of gold deposits in Ukraine are made.